DEVELOPMENT OF MATHEMATICS LEARNING EVALUATION INSTRUMENTS BASED ON WORDWALL FOR PHASE E STUDENTS - Nurul Elenawati; Sri Rezeki; Endang Istikomah; Leo Adhar Effendi; Merry Susanti (UIR PRESS, 2024)
This research is motivated by the need for evaluation instruments because at SMKN 3 Pekanbaru does not hold school exams so that student assessments are taken from daily exercises at the end of learning. This study aims to determine the validity, practicality and learning outcomes of students using wordwall-based evaluation instruments. This type of development research uses the R&D (Reasearch and Development) model which has been modified into 8 stages, namely potential problems, data collection, product design, design validation, design revision, product trials, product revision and trial use. The data collection techniques used in this study were validation sheets, student and teacher response sheets and student learning outcomes tests using wordwall-based evaluation instruments. The research subjects were E phase students of SMKN 3 Pekanbaru. The results of the wordwall-based evaluation instrument validation test were 88.29% with a very valid category. The results of the practicality test of wordwall-based evaluation instruments based on teacher and learner response sheets were 91.75% with a very practical category. The learning outcomes of students using wordwall-based evaluation instruments were 92.59% with a very good category.